The Significance of Sacred Places in the Selected Indigenous Churches in Ekitiland (2012)
Sacred places are non-homogenous sites where the mysteries of nature, the incorporeal and supra sensible essence are encountered. Previous studies recognised the existence of these places in ancient Israel, and examined the socio-religious dimensions of the places, but they have not considered the recognition and patronage of similar places in indigenous churches especially in Ekitiland, whose topography enhances the patronage of sacred places. This study, therefore, examined the functions of sacred waters, grounds and mountains in ancient Israel with reference to the practices of selected indigenous churches in Ekitiland, with a view to highlighting their socio-religious significance. The study was premised on Intercultural Hermeneutic Theory, which accommodates African socio-religious realities in the study of the Bible. Ten assembles each from Christ Apostolic Church (CAC), and African Apostolic Church (AAC), which patronise sacred places, were purposively selected. In-depth interviews were conducted with 150 purposively selected respondents, comprising 20 church leaders, 20 heads of groups and 35 members from both churches in Ajaye, Efon, Erio, Ido-Ile and Ikole communities which host these sacred sites, covering three Local Government areas. Participant observation was also made at 12 worship sessions at purposively selected sacred places. The data collected were subjected to content analysis. Sacred waters, grounds and mountains functioned as worship and healing centres in Israel during the pre-Temple age. River Jordan was reputed for its healing virtues, which was confirmed by the healing of Naman. In Ekitiland, sacred waters, such as omi-Babalola, omi-oni and omi-oluwanifise-CAC served fertility, healing and deliverance purposes; omi-Araromi and omi-Amubiina -A.A.C. were patronised for the healing of festering sores and provision of male children. Theophanic experiences of Jacob, Moses and Joshua at Bethel, Sinai and Jericho grounds, made these sacred grounds patronised worship centres in Israel. Similarly, prayers offered on sacred grounds, such as ile -Agbara reportedly engendered spiritual empowerment, l -Ba al l inspired spiritual visions for the C.A.C.; ile -Agbara was trusted for rain-making and ile - Anu for divine mercy in the AAC. Mount Sinai, in ancient Israel, attained sacred status owing to supernatural manifestations which culminated in the revelation of the Torah. Similarly, mountains such as oke-isegun, oke-iyanu and oke-anu patronised by the C.A.C. were known for overcoming evils, confirmation of pastoral calling and fertility, - in the A.A.C. was popular for divine communication with God and inducing business patronage. All the mountains were believed by both CAC and AAC to be helpful in terms of church resolutions, prophetic revelations, visa procurement, contract awards and security. Consequently, civil servants and businessmen patronised oke-anu for promotion; politicians visited oke-isegun for electoral victory; and pastors and sick people frequented oke- anu and oke-Anu for power and healings. However, noticeable abuses of prophetic gifts, sales of olive oil and extortion, common in Eli’s days, were prevalent. Sacred places performed essentially the same spiritual, economic and social functions in selected indigenous churches in Ekitiland and ancient Israelite liturgies. This shows the link between the doctrines of Christ Apostolic Church, African Apostolic Church and ancient Israelite religion